2019
DOI: 10.3390/jcm8122217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diagnostic and Prognostic microRNAs for Recurrent Vitreous Hemorrhage in Patients with Proliferative Diabetic Retinopathy

Abstract: MicroRNAs (miRNAs) can provide insight into the pathophysiological states of ocular tissues such as proliferative diabetic retinopathy (PDR). In this study, differences in miRNA expression in vitreous from PDR patients with and without incidence of recurrent vitreous hemorrhage (RVH) after the initial pars-plana vitrectomy (PPV) were analyzed, with the aim of identifying biomarkers for RVH. Fifty-four consented vitreous samples were analyzed from patients undergoing PPV for PDR, of which eighteen samples under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
(74 reference statements)
0
22
0
Order By: Relevance
“…The peculiarity of the present study starts from the population examined: as a matter of fact, AH miRNAs were evaluated in T2D patients affected by DME. Previous studies evaluating miRNA expression through intraocular sampling are few in number and all but one were conducted on patients affected by PDR, in the context of either type 1 or type 2 diabetes [ 16 , 17 , 18 , 19 , 20 ]. We enrolled only patients showing DME with mild or moderate NPDR in an attempt to minimize the ischemic component and consequently the molecular pathways driven by ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The peculiarity of the present study starts from the population examined: as a matter of fact, AH miRNAs were evaluated in T2D patients affected by DME. Previous studies evaluating miRNA expression through intraocular sampling are few in number and all but one were conducted on patients affected by PDR, in the context of either type 1 or type 2 diabetes [ 16 , 17 , 18 , 19 , 20 ]. We enrolled only patients showing DME with mild or moderate NPDR in an attempt to minimize the ischemic component and consequently the molecular pathways driven by ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hirota et al [ 18 ] investigated the expression of 168 miRNAs in the vitreous humor of patients with PDR and found that six miRNAs (miR-15a, miR-320a, miR-320b, miR-93, miR-29a and miR-423-5p), related to angiogenesis and fibrosis, are significantly overexpressed in PDR. Mammadzada et al [ 19 ] showed a significant increase in the miRNA-19a, miR-27a, miR-20a and miR-93 expression in PDR patients undergoing PPV as compared to the controls. Recently by next generation sequencing, Chen et al [ 20 ] found seven miRNAs upregulated (miR-150-5p, miR-30c-5p, miR16-2-3p, miR-1827, miR-140-3p and miR-93-5p) and one downregulated (miR-99-5p) in AH of T2D patients with PDR as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ▶ table 1, we have summarized miR-126 [11,12], miR-211 [13], miR-93 [14][15][16], miR-122 [17], miR-221 [18], miR-27b and miR-320a [8], miR-150-5p, miR-21-3p and miR-30b-5p [19] as biomarkers in DR over the past 5 years. At the same time, we have focused on miRNAs in vitreous humor (VH) of DR, such as miR-126 [20], miR-19a and 27a [21], miR-29a [22,23], miR-93 and 20a [21], and miR-200b [24] in ▶ table 2.…”
Section: Circulating Mirnas As Biomakers In Drmentioning
confidence: 99%